Study of microbially-induced carbonate precipitation for improving coarse-grained salty soil. (10th September 2022) - Peng, Erxing; Hu, Xiaoying; Chou, Yaling; Sheng, Yu; Liu, Shihao; Zhou, Fansheng; Wu, Jichun; Cao, Wei
Abstract: The salinity of soil can result in serious potential environmental hazards such as increased collapsibility and corrosiveness. Microbially induced carbonate precipitation is an upcoming and pollution-free treatment modality that can eliminate environmental and engineering hazards of saline soil. To verify the feasibility of the method of curing saline soils, a series of tests were conducted to investigate the impact of chloride salt on urea hydrolysis, the impact of the method on engineering and mechanical properties of coarse-grained soils containing chloride salt and the deterioration mechanism of curing effect caused by salt. The study demonstrated that, even though the curing effect of the method is excellent, the negative effect of salt cannot be ignored. With increased salt concentration, the hydrolysis rate and calcium carbonate precipitation efficiency sharply decrease at first and tend to be flatter. The unconfined compressive strength and shear strength of the samples can be greatly improved through the application of the method. However, calcium carbonate content reduces with an increase in the salt content, which decreases the strength. Compared to uncured samples, the permeability coefficient of cured samples reduced from 1 to 2 orders of magnitude. On the other hand, as the dominant aperture size increases with a decrease in the calcium carbonate content, the permeability coefficient increases with an increase in the salt content. Furthermore, micro-mechanical tests, such as X-ray diffraction and scanning electron microscope tests, were conducted to analyze the mechanism by which salt degrades the reinforcement. As a guiding agent, while chloride salt can improve the proportion of calcite in calcium carbonate, it decreases the total quantity of calcium carbonate through the limiting urea hydrolysis process. A significant amount of calcium carbonate is deposited on the surface of the particles in each sample, especially the contact surface. In conclusion, even though salt has a certain deterioration effect, microbially-induced carbonate precipitation is still an effective and environment-friendly method to cure saline soil. This study can provide a theoretical basis for using this method to solidify saline soil.